Amino acids and mechanistic target of rapamycin regulate the fate of live engulfed cells. Issue 10 (21st September 2021) - Kim, Sung Eun; Zhang, Justin; Jiang, Enoch; Overholtzer, Michael
Abstract: Metabolic stress contributes to the regulation of cell death in normal and diseased tissues. While different forms of cell death are known to be regulated by metabolic stress, how the cell engulfment and killing mechanism entosis is regulated is not well understood. Here we find that the death of entotic cells is regulated by the presence of amino acids and activity of the mechanistic target of rapamycin (mTOR). Amino acid withdrawal or mTOR inhibition induces apoptosis of engulfed cells and blocks entotic cell death that is associated with the lipidation of the autophagy protein microtubule‐associated protein light chain 3 (LC3) to entotic vacuoles. Two other live cell engulfment programs, homotypic cell cannibalism (HoCC) and anti‐CD47 antibody‐mediated phagocytosis, known as phagoptosis, also undergo a similar vacuole maturation sequence involving LC3 lipidation and lysosome fusion, but only HoCC involves mTOR‐dependent regulation of vacuole maturation and engulfed cell death similar to entosis. We further find that the regulation of cell death by mTOR is independent of autophagy activation and instead involves the 4E‐BP1/2 proteins that are known regulators of mRNA translation. Depletion of 4E‐BP1/2 proteins can restore the mTOR‐regulated changes of entotic death and apoptosis rates of engulfed cells. These results identify amino acid signaling and the mTOR‐4E‐BP1/2 pathway as an upstream regulation mechanism for the fate of live engulfed cells formed by entosis and HoCC.